Behaviors Related to Psychiatric Disorders and Pain Perception in C57BL/6J Mice During Different Phases of Estrous Cycle - Zhao, Weinan; Li, Qing; Ma, Yu; Wang, Zhiyong; Fan, Bingqian; Zhai, Xiaojing; Hu, Mengfan; Wang, Qing; Zhang, Moruo; Zhang, Chunyan; Qin, Yixue; Sha, Sha; et al. (Frontiers in Neuroscience, 2021)
Robust sex difference among humans regarding psychiatry- and pain-related behaviors is being researched; however, the use of female mice in preclinical research is relatively rare due to an unchecked potential behavioral variation over the estrous cycle. In the present study, a battery of psychiatry- and pain-related behaviors are examined in female C57BL/6J mice over different estrous cycle phases: proestrus, estrous, medestrous, and diestrous. Our behavioral results reveal that there is no significant difference over different phases of the estrous cycle in social interaction test, forced swim test, sucrose preference test, tail suspension test, open field test, marble burying test, novelty-suppressed feeding test, Hargreave’s thermal pain test and Von Frey mechanical pain test. These findings implicate those mental illnesses- and pain-related behaviors in female C57 BL/6J mice appear to be relatively consistent throughout the estrous cycle. Moreover, the estrous cycle might not be a main contributor to female C57BL/6J mice’s variability of behaviors.